The Characteristics, Long-Term Outcomes, Risk Factors, and Antithrombotic Therapy in Chinese Patients With Atrial Fibrillation and Bioprosthetic Valves - Ren, Jiameng; Yang, Yanmin; Zhu, Jun; Wu, Shuang; Wang, Juan; Zhang, Han; Shao, Xinghui (Frontiers in Cardiovascular Medicine, 2021)
Introduction: There were few data about the clinical profiles and long-term outcomes in Chinese patients with atrial fibrillation (AF) and bioprosthetic valves. Methods: The retrospective study enrolled 903 patients with bioprosthetic valve replacement at our hospital and discharged with a diagnosis of AF from January 2010 to December 2018. Results: The median age was 65.6 (61.9–69.1) years, and 548 (60.7%) patients were women. During a follow-up period of 3.84 (2.64–5.51) years, 68 (1.8 per 100 person-years) patients died, 81 (2.1 per 100 person-years) patients developed thromboembolism, and 23 (0.6 per 100 person-years) patients experienced major bleeding. The CHA2DS2-VASc score, as a categorical variable (low, moderate, or high risk), predicted the risk of thromboembolism with the C-statistic of 0.6 (95% CI: 0.511–0.689, p = 0.046). The incidence of the CHA2DS2-VASc score increment was 11.6 per 100 person-years, and the annual reclassification rate of stroke risk (from a low or moderate group to a higher group) was 12.7%. The current proportion of oral anticoagulants was 52.3, 59, and 63.2%, respectively, in the low, moderate, and high stroke risk groups. Age (OR: 1.04, 95% CI: 1.01–1.06, p = 0.01), left atrial size (OR: 1.05, 95% CI: 1.03–1.08, p < 0.001), and rheumatic heart disease (OR: 1.49, 95% CI: 1.05–2.10, p = 0.025) were positively associated with the use of oral anticoagulants. The history of chronic kidney disease (OR: 0.20, 95% CI: 0.05–0.76, p = 0.018), prior surgical ablation (OR: 0.33, 95% CI: 0.24–0.47, p < 0.001), and antiplatelet agent use (OR: 0.08, 95% CI: 0.05–0.13, p < 0.001) were inversely related to the use of oral anticoagulants. Higher admission estimated glomerular filtration rate (HR: 0.515, 95% CI: 0.311–0.853, p = 0.01), left ventricular ejection fraction (HR: 0.961, 95% CI: 0.931–0.992, p = 0.014), concomitant surgical ablation (HR: 0.348, 95% CI: 0.171–0.711, p = 0.004), and rheumatic heart disease history (HR: 0.515, 95% CI: 0.311–0.853, p = 0.01) were associated with a lower risk of death. Surgical ablation (HR: 0.263, 95% CI: 0.133–0.519, p < 0.001) and oral anticoagulants (HR: 0.587, 95% CI: 0.375–0.918, p = 0.019) were related to a lower risk of thromboembolism. Conclusion: Chinese patients with AF and bioprosthetic valve(s) were relatively young and had a high prevalence of rheumatic heart disease with few comorbidities. The percentage of mitral bioprosthetic valve replacement was high. The proportion of concomitant surgical ablation or surgical left atrial appendage occlusion or exclusion was relatively low. The thromboembolic events were the major long-term adverse events. The anticoagulation therapy was underused in patients at moderate or high stroke risk. The CHA2DS2-VASc score was verified to be used for predicting stroke risk in this population. The stroke risk dynamically changed; it needed to be reestimated once the risk factor changed.